2021
DOI: 10.1136/bmjopen-2021-049941
|View full text |Cite
|
Sign up to set email alerts
|

I had to leave. I had to leave my clinic, my city, leave everything behind in Syria. Qualitative research of Syrian healthcare workers migrating from the war-torn country

Abstract: ObjectivesTo explore the reasons why healthcare workers migrate from Syria, a country where conflict has been raging for over a decade.DesignA qualitative study was performed using semistructured interviews. Semistructured questions guided in-depth interviews. Content analysis was used.SettingParticipants were Syrian healthcare workers who had worked in the country after the conflict started in 2011, but at some point left Syria and settled abroad. The interviews took place in Turkey and Europe in 2016 and 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…The figure is equal regardless of whether HCWs worked under ISIS rule in parts of Syria or NSAG controlled areas [ 12 , 19 , 22 – 24 ]. Our recent study points out that reasons for HCWs to leave to leave Syria were all related to security concerns [ 25 ]. The International Non-Governmental Organizations (INGOs) and most international organisations (IOs) have been forced to evacuate their non-local personnel due to security reasons leaving local workers to operate remotely across the neighbouring countries [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The figure is equal regardless of whether HCWs worked under ISIS rule in parts of Syria or NSAG controlled areas [ 12 , 19 , 22 – 24 ]. Our recent study points out that reasons for HCWs to leave to leave Syria were all related to security concerns [ 25 ]. The International Non-Governmental Organizations (INGOs) and most international organisations (IOs) have been forced to evacuate their non-local personnel due to security reasons leaving local workers to operate remotely across the neighbouring countries [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several international works have reported that armed conflicts decrease the use of health services such as prenatal care, documented in the conflicts in Nepal [ 26 , 27 ]. Sri Lanka [ 28 ], Burundi and Uganda [ 29 ], and the availability of health services and health personnel due to the destruction of infrastructure or because health workers migrate or are killed in the context of these conflicts, as in the cases of Lebanon [ 30 ], Cambodia [ 31 ], Sri Lanka [ 28 ], and Syria [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low quality of life was associated with feelings of hopelessness and depressive symptoms among Palestinians in the West Bank (Mahamid et al, 2022). Kallström et al (2021) explored the reasons why healthcare workers migrate from Syria, and they found that feelings of constant fear and insecurity are considered the main reasons for healthcare workers' migration from Syria. Rafiq et al (2022) studied the causes of the temporary migration of workers from Khyber-Pakhtunkhwa, Pakistan, to Saudi Arabia and found poverty, un/employment, income wage differentials, turbulent and unstable environment, the most reasons for Pakistanis' migration to Saudi Arabia.…”
Section: Desire To Migrate Psychological Well-being and Quality Of Lifementioning
confidence: 99%
“…The current study examines the relationship between trauma symptoms, desire to migrate, and psychological well-being and whether general belongingness, belongingness to place and quality of life mediate the association between the three variables among Palestinian adults living in the West Bank of occupied Palestine, East Jerusalem, and Gaza Strip. Based on prior research (Balcilar & Nugent, 2019; El-Khodary et al, 2020; Hamdan & Hallaq, 2021; Kallström et al, 2021; Khawaja, 2012; Koikkalainen et al, 2020; Kunuroglu et al, 2018; Rafiq et al, 2022; Thabet, 2017; Theodori & Theodori, 2014), three study hypotheses were defined: (a) Trauma symptoms would be positively associated with the desire to migrate; (b) trauma symptoms would be negatively associated with psychological well-being, general belongingness, belongingness to place and quality of life; and (c) quality of life, general belongingness, and belongingness to place would be mediating the association between trauma symptoms, desire to migrate, and psychological well-being.…”
Section: Trauma Psychological Well-being and Desire To Migratementioning
confidence: 99%